MommyHood a retractable breastfeeding cover that encourages a more regular breastfeeding practice in public places catered for first-time young mothers - Federico, Jubilee Annie L.; Dela Peña, Fortunato Jr. B. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2023)
Breastfeeding is widely recognized as the optimal method of infant feeding, offering numerous health benefits for both the mother and child. However, despite its advantages, many women face challenges in practicing breastfeeding, particularly in public spaces due to social stigma and discomfort. This thesis aims to explore the impact of breastfeeding covers as a tool to promote regular breastfeeding practice in public setting.

This study combines qualitative interviews and quantitative surveys to gather comprehensive data. The qualitative phase involves interviews with breastfeeding mothers to understand their experiences, perceptions, and challenges associated with breastfeeding in public. These interviews shed light on the social, cultural, and psychological factors that influence women's decisions to breastfeed in public. Additionally, the quantitative phase involves administering surveys to breastfeeding individuals regardless of their age, to gauge their attitudes and opinions regarding public breastfeeding covers and to compare with the target audience of this study. The survey results help identify societal perceptions, concerns, and expectations surrounding the use of breastfeeding essentials that will help improve their practice.

The study also examines the design and functionality of existing breastfeeding covers and proposes innovative solutions that address the needs and preferences of breastfeeding mothers. By considering factors such as ease of use, comfortable, good coverage, compact or portable, regulate thermal body temperature, unrestrict movement and multi-functionality, a breastfeeding cover that enables moms to breastfeed anywhere they are can be created while also ensuring the privacy of both the mother and the child.

The findings of this thesis contribute to the existing body of knowledge on breastfeeding practices and offer practical recommendations for policymakers, healthcare professionals, and designers to promote regular breastfeeding in public spaces. The outcomes of this research have the potential to create supportive environments that facilitate breastfeeding and contribute to the overall well-being of infants and mothers.
Thesis (Bachelor of Fine Arts in Industrial Design)--University of the Philippines Diliman
Bibliography: leaves 70-71
Keywords: Breastfeeding; Mother and infant; Breastfeeding promotion